FAKTOR-FAKTOR PENDORONG KONSUMSI MUSIK GENRE METAL PADA GENERASI MILLENNIAL BERDASARKAN PRINSIP HEAVINESS - Riyandi Aminul Rasyid; Dessy Kurnia Sari; Donard Games (Journal Publicuho, 2024)
This study aims to detect several factors that drive millennials to consuming metal genre music based on the heaviness principle and determine dominant sub-genre which millennials preferred and self-emotional on each. By using a qualitative approach throughout semi-structural interviews for 20 millennials with a snowball sampling technique, then analyzed by thematic analysis. Results found that the driving factors of millennials to consuming musicals with the metal genre start from knowing metal music, then using it as a means of expression, continuing to participate in events, bands and communities, then exploring subgenres, artistic as well as emotional expression.